2020
DOI: 10.3390/ijerph17217959
|View full text |Cite
|
Sign up to set email alerts
|

A Sisterhood of Hope: How China’s Transgender Sex Workers Cope with Intimate Partner Violence

Abstract: Transgender sex workers (TSWs/TSW) face considerable challenges that affect their mental health and make their situations more vulnerable and precarious. TSWs often experience violence from clients, police, and others, but it is estimated that 50% of these acts of violence are at the hands of their intimate partners. The marginalization of TSWs is fueled by abuse through isolation and shaming which prevents them from seeking help through formal channels like police or counselling services. There is limited res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…18,[20][21][22] Eight research articles recruited both cisgender and TGNC participants, 19,20,[23][24][25][26][27][28] and five were on TGNC individuals. 8,12,[29][30][31] 14 research articles were on transgender women only, 14,[32][33][34][35][36][37][38][39][40][41][42][43][44] among which, seven articles were on transgender women sex workers (TWSW). 33,[37][38][39]41,42,44 Most articles were collected in first or second-tier cities in mainland China (metropolitan cities).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,[20][21][22] Eight research articles recruited both cisgender and TGNC participants, 19,20,[23][24][25][26][27][28] and five were on TGNC individuals. 8,12,[29][30][31] 14 research articles were on transgender women only, 14,[32][33][34][35][36][37][38][39][40][41][42][43][44] among which, seven articles were on transgender women sex workers (TWSW). 33,[37][38][39]41,42,44 Most articles were collected in first or second-tier cities in mainland China (metropolitan cities).…”
Section: Resultsmentioning
confidence: 99%
“…8,12,[29][30][31] 14 research articles were on transgender women only, 14,[32][33][34][35][36][37][38][39][40][41][42][43][44] among which, seven articles were on transgender women sex workers (TWSW). 33,[37][38][39]41,42,44 Most articles were collected in first or second-tier cities in mainland China (metropolitan cities). Eleven articles collected data from multiple sites.…”
Section: Resultsmentioning
confidence: 99%
“…The TSWs in the sample reported that they all first wanted to become a woman when they were teenagers or pre-teens. They each had to find their own way to reconcile the overwhelming desire to become feminine, despite the stigma associated with rejecting one’s assigned sex [ 7 ]. All 49 TSWs said that embracing their femininity helped them maintain mental health.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The conventional literature involving relationships between clients and sex workers has typically examined female sex workers and heterosexual male clients [ 3 , 4 ]. The literature on TSWs tends to focus on negative aspects, such as portraying them as victims of discrimination and violence [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] or victims of HIV and STDs [ 12 , 13 , 14 , 15 ]. Thus, the literature calls for studies to examine how TSWs deal with stigma and discrimination as well as engage in relationships with their clients—and perhaps, more importantly—with their intimate sex partners [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hukou encourages marginalization and tropicality The household registration system (hukou) is a key factor encouraging the marginalization and rural/urban segregation faced by the male sex workers (Kong, 2012;Tsang, 2017;Tsang, 2018;Tsang, 2020a). The household registration system also provides a permanent identification number, comparable to a social security number in the United States or the systems of permanent identification cards used in many other countries.…”
Section: Commodifying Rural Queer Bodies With Urban Embodimentsmentioning
confidence: 99%